Iatrogenic risk factors associated with hospital readmission of elderly patients: A matched case‐control study using a clinical data warehouse. (14th February 2018) - Schwab, C.; Korb‐Savoldelli, V.; Escudie, J. B.; Fernandez, C.; Durieux, P.; Saint‐Jean, O.; Sabatier, B.
Summary: What is known: Hospital readmission within 30 days of patient discharge has become a standard to judge the quality of hospitalizations. It is estimated that 14% of the elderly, people over 75 years old or those over 65 with comorbidities, are at risk of readmission, of which 23% are avoidable. It may be possible to identify elderly patients at risk of readmission and implement steps to reduce avoidable readmissions. Objective: The aim of this study was to identify iatrogenic risk factors for readmission. The secondary objective was to evaluate the rate of drug‐related readmissions (DRRs) among all readmissions and compare it to the rate of readmissions for other reasons. Methods: We conducted a retrospective, matched, case‐control study to identify non‐demographic risk factors for avoidable readmission, specifically DRRs. The study included patients hospitalized between 1 September 2014 and 31 October 2015 in an 800‐bed university hospital. We included patients aged 75 and over. Cases consisted of patients readmitted to the emergency department within 30 days of initial discharge. Controls did not return to the emergency department within 30 days. Cases and controls were matched on sex and age because they are known as readmissions risk factors. After comparison of the mean or percentage between cases and controls for each variable, we conducted a conditional logistic regression. Results: The risk factors identified were an emergency admission at the index hospitalization, returning home after discharge, a history of unplanned readmissions and prescription of nervous system drugs. Otherwise, 11.4% of the readmissions were DRRs, of which 30% were caused by an overdose of antihypertensive. The number of drugs at readmission was higher, and potentially inappropriate medications were more widely prescribed for DRRs than for readmissions for other reasons. What is new and conclusion: In this matched case‐control retrospective study, after controlling for gender and age, we identified the typical profile of elderly patients at risk of readmission. These patients had an unplanned admission at the index hospitalization and prescribed nervous system drugs at discharge from the index admission; they have a history of unplanned readmission within 30 days and return home after discharge. Abstract : In this matched case‐control retrospective study, we identified the typical profile of elderly patients at risk of readmission. These patients had an unplanned admission at the index hospitalization and prescribed nervous system drugs, a history of unplanned readmission within 30 days and return home after discharge.